Artificial Regeneration of Santalum album in Rajasthan - Mathur, C. M. (Indian Forester, 1961)
Attempts at artificial regeneration of Santalum album in suitable localities of Rajasthan have been described. Interim results are presented. Sowing of seeds of Mysore origin has given good results.